Το Μεσαιωνικό Αγγελόκαστρο της Κορινθίας. Κάστρο-οικισμός, αγροτική οικονομία - ΚΟΡΔΩΣΗΣ Αλεξανδρος M. (Byzantina Symmeikta, 2021)
Angelokastron is one of the castles in the Frankish castellania of Corinth, holding a strategic position in the mountainous area separating Corinthia from Argolida, on the route leading from Corinth to Epidaurus. The name is attested in catalogues of castles of the period pertaining to the end of the Middle Ages and the beginnings of Ottoman rule as well as in a cadastre of the feudal family of Acciaiuoli (1365), who possessed the Corinthian castellania during the second half of the 14th century. Angelokastro was part of a broader tax unit comprising the nearby castles of Πιάδα/Piada and Λιγουριό/Ligourio. Part of the agricultural production that belonged to the feudal overlord was collected and stored in these castles. During the late medieval and early Ottoman periods, Angelokastro was the main settlement of the peninsula that ends up in Cape Speiraio/Σπείραιο, suggesting that the center of the region mentioned above had moved from the area of Sofiko (where another important medieval castle thrived in the 12th and 13th centuries). Until the 1970s, Angelokastro remained an important settlement, second in size only to the most important village of Sofiko, within the administrative boundaries of the former municipality of Solygia (Σολυγεία).